1999
DOI: 10.1046/j.1464-5491.1999.00010.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of effects of captopril used either alone or in combination with a thiazide diuretic on insulin action in hypertensive Type 2 diabetic patients: a double‐blind crossover study

Abstract: Combination of bendrofluazide with captopril lowered blood pressure but resulted in deleterious effects on insulin action compared to captopril alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 41 publications
1
13
0
1
Order By: Relevance
“…21,27 It has been suggested that because of the potential positive impact of ACE inhibition on insulin action, combining diuretics with ACE inhibitor may in part ameliorate adverse effects of thiazides; 28 however, in patients with essential hypertension, there was still a negative effect when high-dose bendrofluazide was combined with captopril. 9 In hypertensive type 2 diabetic patients, both conventional (2.5 mg) 29 and low-dose (1.25 mg) bendroflumethiazide 11 combined with captopril, when compared with captopril alone, resulted in increased insulin resistance. The current study aimed to establish whether these negative effects were also present when lowdose thiazide in combination with ACE inhibitor was given to nondiabetic patients with essential hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…21,27 It has been suggested that because of the potential positive impact of ACE inhibition on insulin action, combining diuretics with ACE inhibitor may in part ameliorate adverse effects of thiazides; 28 however, in patients with essential hypertension, there was still a negative effect when high-dose bendrofluazide was combined with captopril. 9 In hypertensive type 2 diabetic patients, both conventional (2.5 mg) 29 and low-dose (1.25 mg) bendroflumethiazide 11 combined with captopril, when compared with captopril alone, resulted in increased insulin resistance. The current study aimed to establish whether these negative effects were also present when lowdose thiazide in combination with ACE inhibitor was given to nondiabetic patients with essential hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, studies comparing treatment of an ACE inhibitor with the combination of this ACE inhibitor with high-dose diuretic showed deterioration of IS with the combination in spite of the presence of the ACE inhibitor [18]. Collectively, these findings suggest an adverse effect of diuretics on IS, but because most of these studies were rather small and short in duration [13][14][15][16]18] the possibility that different diuretic doses had different effects on IS requires further investigation.…”
Section: Antihypertensive Agents and Insulin Sensitivitymentioning
confidence: 99%
“…Collectively, these findings suggest an adverse effect of diuretics on IS, but because most of these studies were rather small and short in duration [13][14][15][16]18] the possibility that different diuretic doses had different effects on IS requires further investigation.…”
Section: Antihypertensive Agents and Insulin Sensitivitymentioning
confidence: 99%
“…A potential mechanism by which inhibition of the RAS can improve glucose tolerance or insulin sensitivity is that of amelioration of the diuretic-induced hypokalemia; however, studies have demonstrated that diuretics can impair peripheral insulin sensitivity independent of lowering serum potassium levels [2,7,1113]. Combination RAS blockade (ACE-I or ARB) with diuretic therapy has been reported to cause fewer adverse effects on glucose metabolism than diuretic therapy alone [1315]; however, in some of these studies, the negative metabolic effects of diuretics were not completely ameliorated by RAS blockade [8,11,1617]. …”
Section: Introductionmentioning
confidence: 99%